2018
DOI: 10.1557/adv.2018.519
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Friction of Graphene

Abstract: Despite being one of the oldest phenomena known to mankind and its vast use, there still are open questions about the frictional process between two surfaces, especially at the nanometer scale, such as the energy dissipation mechanism, the influence of the crystallographic orientation and the correlation between macroscopic and microscopic scales. In this work, we analyze the interaction between a sharp tip and graphene by friction force microscopy. The graphene surface roughness and adhesion forces with the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…It has been shown that temperature indeed plays a significant role in the tribological behavior of graphene, as the temperature increases so does the surface roughness and the graphene sheet deformation 42 . As for the second condition, a consequence could be a correlation between adhesion and the measured friction, however previous results do not reinforce this idea 43,44 .…”
Section: Discussionmentioning
confidence: 77%
“…It has been shown that temperature indeed plays a significant role in the tribological behavior of graphene, as the temperature increases so does the surface roughness and the graphene sheet deformation 42 . As for the second condition, a consequence could be a correlation between adhesion and the measured friction, however previous results do not reinforce this idea 43,44 .…”
Section: Discussionmentioning
confidence: 77%
“…In the recent past, graphene has attracted considerable attention as a potential ultrathin material for surface protection, i.e., it modifies the friction, wear, and corrosion. , Nanoscale tribological studies have shown the thickness dependence of friction in graphene, viz., the coefficient of friction (COF) decreases with increasing number of graphene layers from 1 to 4. , The nanoscale friction and wear behaviors of graphene-coated diverse surfaces, measured using atomic/friction force microscopy (AFM/FFM), have also been studied where graphene contributed to the reduction of friction and wear. In general, in graphene’s tribology, the main focus is on its nanoscale tribology so far.…”
Section: Introductionmentioning
confidence: 99%
“…Although such analysis is widely employed in friction and adhesion studies, ,, other studies have reported that friction and adhesion exhibit opposite trends. Therefore, fundamental questions remain about how closely interfacial adhesion can be correlated to friction. Experimentally, adhesion is determined by measuring the force needed to separate contacting bodies while applying a tensile stress to the contact along the direction normal to the interface.…”
mentioning
confidence: 99%